Perancangan Aplikasi Sistem Pemesanan Corrugated Box - Abdul Jabbar (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2022)
Ordering is one of the buying and selling activities carried out by a company. With technology, it is possible to order not only face-to-face, but can be done anywhere and anytime. This thesis aims to build a website-based Corrugated Box Ordering Information System to assist corrugated box ordering activities at CV Hana Citra Buana. This information system is built using the PHP programming language with codeigniter framework for the back-end and bootstrap framework for the front-end. This system was developed using the SDLC (System Development Life Cycle) method with spiral model. The final stage of the development of this system is to test the system using UAT (User Acceptance Testing). Based on the test results, the Corrugated Box Ordering Information System is running well and in accordance with its business processes with aan eligibilty percentage of 90,94%.